Harmonisation projects: Lessons from the European experience - Cartwright, J (Faculty of Law, Adolfo Ibáñez University, 2018)
In recent years a number of different projects of harmonisation of private law, and in particular contract law, have been developed at both the regional level and the international level. In Europe for twenty-five years efforts were made to work out a possible model for the harmonisation of contract law: by the end of 2014 this appeared not to have succeeded, but there are lasting results of the process which had a significant influence in the process of the reform of the law of contract in France in 2016. This illustrates the value which such projects can have, and can provide a lesson for other regions such as Latin America.